Determining Triaxial Stress Sensitivity of Oil Reservoir Rocks without Fluid Flooding. (15th April 2021) - Li, Zhihang; Hu, Xiong
Abstract : The sensitivity of oil reservoir rocks to stress is the basis for oilfield development, which determines the production method employed in the field. Therefore, it is critical to understand the stress sensitivity behavior of oil reservoir rocks in an oilfield. In this paper, a novel method for determining the stress sensitivity of oil reservoir rocks by triaxial stress testing without fluid flooding was proposed. It measures the triaxial stress and strain of the core rock samples, and based on which, the core porosity and permeability under stress can be evaluated by theoretical model. In the model, the pores of the core were assumed to be a bundle of capillaries and the necessary relationship was derived to calculate the changes of porosity and permeability of the core samples caused by the strain. Through comparison with and analysis of experimental results obtained for various rock core samples under different stress and strain conditions, it is observed that the theoretical model match well with that of the experiments. This method provides a new approach for the stress sensitivity analysis of oil reservoirs without fluid flooding.